2008
DOI: 10.1002/ldr.848
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbiochemical properties as indicators for success of heathland restoration after military disturbance

Abstract: Decline of heathlands in Central Europe raises the question of successful restoration of degraded heathlands. We examined the impact of different restoration techniques on soil microbial biomass carbon (C mic ) and nitrogen (N mic ) and enzyme activity on an abandoned military training site in the Lüneburger Heaths. The aim was to determine which technique resulted in typical heathland soil conditions. The training site was in use for about 50 years. Vegetation and soils were degraded in large areas. Restorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…By 2013, GFGP had reestablished forests for about 27.8 million ha and most of the restored forests are monocultures and compositionally simple mixed plantations (Hua et al 2016). The aim of vegetation recovery is not only the establishment of sustainable plant communities (Orozco-Aceves et al 2017) and improvement of soil physicochemical properties (Gasch et al 2014), but also the development of the soil microbes (Heitkamp et al 2008). Traditional recovery measures mainly concentrate on colonization and investigation of aboveground vegetation communities.…”
Section: Introductionmentioning
confidence: 99%
“…By 2013, GFGP had reestablished forests for about 27.8 million ha and most of the restored forests are monocultures and compositionally simple mixed plantations (Hua et al 2016). The aim of vegetation recovery is not only the establishment of sustainable plant communities (Orozco-Aceves et al 2017) and improvement of soil physicochemical properties (Gasch et al 2014), but also the development of the soil microbes (Heitkamp et al 2008). Traditional recovery measures mainly concentrate on colonization and investigation of aboveground vegetation communities.…”
Section: Introductionmentioning
confidence: 99%
“…Available soil N mainly comes from the mineralization of organic N (Binkley and Hart, 1989;Vestgarden and Kjønaas, 2003). Soil N availability directly influences the productivity of terrestrial ecosystems (Reich et al, 1997); in addition, N availability impacts plant biodiversity, community succession, and long-term ecosystem resilience (Schlesinger, 1997;Heitkamp et al, 2008). Although the classical N mineralization paradigm of N cycling may be incomplete, and many studies have shown that plants can use amino acids and other organic N forms (Schimel and Bennett, 2004), soil N mineralization is still an important criterion for evaluating forest N cycling (Loreau, 1994;Larsen, 1995;Schlesinger, 1997;Chen et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%